Potassium‐Assisted Fabrication of Intrinsic Defects in Porous Carbons for Electrocatalytic CO2 Reduction - Ling, Li‐Li; Jiao, Long; Liu, Xiaoshuo; Dong, Yun; Yang, Weijie; Zhang, Hongjun; Ye, Bangjiao; Chen, Jun; Jiang, Hai‐Long (Advanced materials (Weinheim), 2022)
The fabrication of intrinsic carbon defects is usually tangled with doping effects, and the identification of their unique roles in catalysis remains a tough task. Herein, a K+‐assisted synthetic strategy is developed to afford porous carbon (K‐defect‐C) with abundant intrinsic defects and complete elimination of heteroatom via direct pyrolysis of K+‐confined metal–organic frameworks (MOFs). Positron‐annihilation lifetime spectroscopy, X‐ray absorption fine structure measurement, and scanning transmission electron microscopy jointly illustrate the existence of abundant 12‐vacancy‐type carbon defects (V12) in K‐defect‐C. Remarkably, the K‐defect‐C achieves ultrahigh CO Faradaic efficiency (99%) at −0.45 V in CO2 electroreduction, far surpassing MOF‐derived carbon without K+ etching. Theoretical calculations reveal that the V12 defects in K‐defect‐C favor CO2 adsorption and significantly accelerate the formation of the rate‐determining COOH* intermediate, thereby promoting CO2 reduction. This work develops a novel strategy to generate intrinsic carbon defects and provides new insights into their critical role in catalysis. A K+‐assisted synthetic strategy is developed to afford porous carbon (K‐defect‐C‐1100) with abundant 12‐vacancy‐type (V12) carbon defects via direct pyrolysis of a K+‐confined metal–organic framework (K+@bio‐MOF‐1) at 1100 °C. Strikingly, the K‐defect‐C‐1100 presents excellent electrocatalytic CO2 reduction activity with ultrahigh CO Faradic efficiency up to 99% at −0.45 V, far surpassing the N‐doped carbon (N‐C‐1100) counterpart.